Self Efficacy Mediates Green Education And Environmental Concern Towards Sustainable Entrepreneurial Intentions: Efikasi Diri Memediasi Pendidikan Hijau Dan Kepedulian Lingkungan Terhadap Niat Kewirausahaan Berkelanjutan - Salman Awaludin; Siti Shoimah; Martha Laila Alisandra (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Environmental sustainability increasingly integrates with modern business development through sustainable entrepreneurship models. Specific Background Within higher education, university students demonstrate substantial potential to develop green commercial ventures supported by their academic competencies. Knowledge Gap However, the relationship connecting ecological education and environmental concern to sustainable business creation is not always direct, necessitating a psychological bridging mechanism. Aims This study investigates the formation of green entrepreneurial intentions among university students by positioning self-efficacy as a critical mediating variable. Results Utilizing Structural Equation Modeling-Partial Least Squares on purposively sampled students, the quantitative analysis demonstrates that both green entrepreneurship education and environmental concern positively determine self-efficacy and green entrepreneurial intentions. Furthermore, self-efficacy successfully mediates the relationship between educational exposure, ecological awareness, and the ultimate intention to establish sustainable ventures. Novelty This research distinctly integrates formal green business education and ecological concern within a specific self-efficacy mediation framework to explain the psychological progression of student entrepreneurial intentions. Implications Consequently, higher education institutions must systematically integrate ecological sustainability into business curricula to build self-efficacy and successfully cultivate a new generation of environmentally responsible entrepreneurs. Highlights Green entrepreneurship education and environmental concern positively determine student self-efficacy. Self-efficacy successfully mediates the relationship between ecological awareness and sustainable business intentions. Higher education institutions must integrate sustainability into business curricula to build entrepreneurial confidence. Keywords Green Entrepreneurial Intentions; Sustainable Entrepreneurship Education; Environmental Concern; Self Efficacy Mediation; Higher Education Curricula